The Effect of Environmental Sustainabiity and Value Chain Concept in the Context of Local Economy on Value Added of Coffee Commodities in Kerinci - Heppi Syofya (Westscience Press, 2023)
This study examines the relationship between environmental sustainability, the value chain concept, and local economic development in the context of value-added commodity coffee in Kerinci, Indonesia. The research adopts a mixed-methods approach, incorporating qualitative interviews with key stakeholders and quantitative surveys of coffee producers and consumers. The findings reveal that coffee producers in Kerinci have increasingly embraced sustainable practices, such as shade-grown coffee, organic farming, water conservation, and reforestation efforts. These sustainable practices contribute to environmental preservation and enhance the value chain dynamics, leading to improved market access and increased value addition for coffee producers. Moreover, the study identifies a positive correlation between sustainable practices, value chain integration, and local economic indicators, indicating that sustainable coffee production promotes local economic development in Kerinci. The study recommends strengthening support mechanisms, promoting market access and value addition, fostering collaboration and knowledge exchange, and enhancing policy and institutional support to further enhance the environmental sustainability and economic competitiveness of the coffee industry in Kerinci.